Association among COVID-19, multisystem inflammatory syndrome in children, and oral health status - Gülser KILINÇ; Aliye AKCALI; Nurşen BELET; Bilge Cansu UZUN; Şilem Özdem ERBAŞ; İrem Ceren ARSLAN; Ayşe Çakıl GÜZIN (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The pathophysiology of multisystem inflammatory syndrome in children (MIS-C) and associated oral symptoms have not been clarified yet. The aim of the present study was to compare the oral health status of children with MIS-C-associated Coronavirus disease 2019 (COVID-19) and COVID-19. A total of 54 children with SARS-CoV-2 infection, 23 with MIS-C-associated COVID-19 and 31 with asymptomatic, mild, and moderate COVID-19 were recruited for the present cross-sectional study. Sociodemographic variables, medical examinations, oral hygiene habits, and extraoral and intraoral findings (DMFT/dmft index, OHI scores, and oral mucosal changes) were recorded. The t-test for independent samples and the Mann-Whitney U test were used (p < 0.05). MIS-C was found to be associated with chapped lips (all patients) and oral mucosal changes, including erythema, white lesion, strawberry tongue, and swelling of the gingiva as compared to the COVID-19 group (frequency of more than one mucosal change: 100% vs. 35%) (p < 0.001). Children with MIS-C presented higher DMFT/dmft scores (DMFT/dmft 5.52 ± 3.16 for the MIS-C group vs. 2.26 ± 1.80 for the COVID-19 group) (p < 0.01). Elevated OHI scores were also associated with MIS-C (mean ± SD: 3.06 ± 1.02 (MIS-C) vs. 2.41 ± 0.97 (COVID-19) (p < 0.05). Oral manifestations, mainly strawberry and erythematous tongue, were characteristic features of MIS-C. Prevalence of oral/dental symptoms was elevated in children with MIS-C when compared to COVID-19. Therefore, dental professionals should be aware of the oral manifestations associated with MIS-C, which may have high mortality and morbidity rates.